Assessing the Feasibility of Measuring Variation in Facility Design Among American Childbirth Facilities. (April 2019) - Plough, Avery; Polzin-Rosenberg, Deb; Galvin, Grace; Shao, Amie; Sullivan, Brendan; Henrich, Natalie; Shah, Neel T.
Objective: To assess the feasibility of quantifying variation in childbirth facility design and explore the implications for childbirth service delivery across the United States. Background: Design has been shown to impact quality of care in childbirth. However, most prior studies use qualitative data to examine associations between the design of patient rooms and patient experience. There has been limited exploration of measures of unit design and its impact on care provision. Method: We recruited 12 childbirth facilities that were diverse with regard to facility type, location, delivery volume, cesarean delivery rate, and practice model. Each facility provided annotated floor plans and participated in a site visit or telephone interview to provide information on their design and clinical practices. These data were analyzed with self-reported primary cesarean delivery rates to assess associations between design and care delivery. Results: We observed wide variation in childbirth unit design. Deliveries per labor room per year ranged from 75 to 479. The ratio of operating rooms to labor rooms ranged from 1:1 to 1:9. The average distance between labor rooms and workstations ranged from 23 to 114 ft, and the maximum distance between labor rooms ranged from 9 to 242 ft. More deliveries per room, fewer labor rooms per operating room, and longer distances between spaces were all associated with higher primary cesarean delivery rates. Conclusions: Clinically relevant differences in design can be feasibly measured across diverse childbirth facilities. The design of these facilities may not be optimally matched to service delivery needs.